P252 Assessment of ulcerative colitis using histological indexes. (16th January 2018) - Magro, F; Lopes, J; Borralho, P; Lopes, S; Coelho, R; Cotter, J; Dias de Castro, F; Sousa, H T; Lago, P; Salgado, M; Andrade, P; Vieira, A I; et al.
Abstract: Background: Histological remission is being increasingly acknowledged as a therapeutic endpoint in ulcerative colitis (UC) patients. Our work aimed: i) to evaluate the agreement between three histological classification systems – Geboes score (GS), Nancy index (NI) and Robarts histopathology index (RHI); ii) to relate these scoring systems with the patients' endoscopic outcomes and inflammation burden; iii) to unveil which (if any) histological features could be predicted from FC levels. Methods: Biopsy samples from 377 UC patients were blindly evaluated using GS, NI and RHI. The results were compared with the patients' Mayo endoscopic score and FC levels. Results: GS, NI and RHI have a good concordance concerning the distinction between patients in histological remission or activity. In fact, using the GS with a 3.1 cut-off as the reference, 87 and 71% of the patients with histological activity and 89 and 100% of the patients in histological remission, were correctly identified by the NI and RHI, respectively. These scores could also predict the Mayo endoscopic score and the FC levels, with their sensitivity and specificity levels depending on the chosen cut-offs. For FC levels higher than 250 μg/g, all scores presented a negative predictive value (NPV) between 76–88%, while for a Mayo Score of 1 the NPV was 100% for all scores. Moreover, the presence of neutrophils in the lamina propria did not associate with FC levels. Conversely, higher FC levels were statistically associated with the presence of neutrophils in the epithelium, as well as with ulceration or erosion of the intestinal mucosa. Conclusions: The classical GS is accurate concerning the newly-developed and formally validated NI and RHI scores. Additionally, FC levels are increased when neutrophils are present in the epithelium and the intestinal mucosa has erosions or ulcers.